2004
DOI: 10.1111/j.0269-8463.2004.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulating form and function of root systems: efficiency of nitrate uptake is dependent on root system architecture and the spatial and temporal variability of nitrate supply

Abstract: Summary1. Root-system architecture, and plastic variation in architecture and physiological function, influence the capacity of plants to acquire nutrients from non-uniform soil. Previous theoretical analyses of the relationship between root architecture and nutrient acquisition have largely assumed uniform soils and unresponsive root systems. We extend these studies by considering non-uniform nutrient supply and plasticity in root growth and uptake physiology. 2. Using modelling, we investigated the growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 32 publications
0
58
0
Order By: Relevance
“…Dunbabin et al (2006Dunbabin et al ( , 2002 predicted water and nutrient uptake, in the presence of exudates (Dunbabin et al 2006), by integrating RootMap into a simulation environment. Dunbabin et al (2004) analysed the effect of different root system architectures on nitrate uptake efficiency. Walk et al (2006) used SimRoot to assess the trade off effects of different root system morphologies on phosphorus acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Dunbabin et al (2006Dunbabin et al ( , 2002 predicted water and nutrient uptake, in the presence of exudates (Dunbabin et al 2006), by integrating RootMap into a simulation environment. Dunbabin et al (2004) analysed the effect of different root system architectures on nitrate uptake efficiency. Walk et al (2006) used SimRoot to assess the trade off effects of different root system morphologies on phosphorus acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Rooting depth is important for the acquisition of mobile nutrients, including nitrate and sulfate, particularly in soils with high leaching potential. Evidence for this comes from modeling studies, where it has been shown that deeper roots could significantly improve the acquisition of nitrogen (Dunbabin et al, 2004;Postma and Lynch, 2011b;Dathe et al, 2013). Reduced CCFN also may affect root hydraulic conductivity, because a smaller radial path Figure 9.…”
mentioning
confidence: 99%
“…The uptake efficiency is dependent on the root system architecture (Dunbabin et al 2004), and specific software have been developed for analysis (Armengaud et al 2009;Ristova et al 2013;Galkovskyi et al 2012). It has long been known that root architecture and plasticity reveal a response of plants to scarce nutrients, and natural variation exists for these traits in different species, related to potassium (Kellermeier et al 2013;Jia et al 2008), nitrogen (De Pessemier et al 2013, and phosphorus availability (Wang et al 2010).…”
Section: Investigation Of Natural Variation In Plants Reveals Differementioning
confidence: 99%